EGFR is a pivotal player of the E2/ERβ – mediated functional properties, aggressiveness, and stemness in triple‐negative breast cancer cells. (31st October 2021) - Kyriakopoulou, Konstantina; Kefali, Elena; Piperigkou, Zoi; Riethmüller, Christoph; Greve, Burkhard; Franchi, Marco; Götte, Martin; Karamanos, Nikos K.
Abstract : Triple‐negative breast cancer (TNBC) is defined by aggressive behavior, limited response to chemotherapy and lower overall survival rates. The increased metastatic potential of TNBC is a combined result of extensive extracellular matrix (ECM) remodeling that leads to cytoskeleton rearrangement and activation of epithelial‐to‐mesenchymal transition (EMT). The overexpression of epidermal growth factor receptor (EGFR) in TNBC tumors has been linked to induced expression of EMT‐related molecules. EMT activation has often been associated with increased metastasis and stemness. Recently, we described the crucial role of EGFR/estrogen receptor beta (ERβ) interplay in the regulation of invasion and cell–matrix interactions. In this study, we report on the EGFR‐ERβ functional relationship in connection to the aggressiveness and cancer stem cell (CSC)‐like characteristics of TNBC cells. ERβ‐suppressed and MDA‐MB‐231 cells were subjected to downstream EGFR inhibition and/or estradiol stimulation to assess alterations in functional parameters as well as in morphological characteristics, studied by scanning electron, atomic force, and immunofluorescence microscopies. Moreover, the expression and localization of key EMT and CSC‐related markers were also evaluated by real‐time qPCR, immunofluorescence microscopy, and flow cytometry. EGFR inhibition resulted in an overall suppression of aggressive functional characteristics, which occurred in an ERβ‐mediated manner. These changes could be attributed to a reduction, at the molecular level, of EMT and stemness‐linked markers, most notably reduced expression of Notch signaling constituents and the cell surface proteoglycan, syndecan‐1. Collectively, our study highlights the importance of EGFR signaling as a key effector of aggressiveness, EMT, and stemness in an ERβ‐dependent way in TNBC. Abstract : In TNBC, EGFR signaling and E2 activation of ERβ advance motility, growth, and angiogenesis and regulate EMT stimulation and matrix composition, which lead to increased stemness. ERβ suppression and EGFR inhibition evoke alterations in the metastatic potential and CSC‐like characteristics of TNBC cells, hence highlighting EGFR signaling as a crucial effector of aggressiveness and stemness in an ERβ‐dependent way. Created with BioRender.com .